Coupling of homotopy perturbation and modified Lindstedt-Poincaré methods for traveling wave solutions of the nonlinear Klein-Gordon equation - Mohyud-Din, Syed Tauseef; Yildirim, Ahmet; İnç, Mustafa (Elsevier B.V., 2012)
oupled method of He's homotopy perturbation method and modified Lindstedt-Poincaré method is applied to the search for traveling wave solutions of a variety of Klein-Gordon equations. The results obtained provide confirmation for the validity of the coupled method. © 2010.
Keywords: Homotopy perturbation method; Klein-Gordon equation; Modified Lindstedt-Poincaré method